Visuomotor dysconnectivity as a candidate mechanism of psychomotor agitation in major depression - Pokorny, Victor Joseph; Anderson, Zachary; Letkiewicz, Allison M.; Hirjak, Dusan; Walther, Sebastian; Shankman, Stewart; Mittal, Vijay (Psychological medicine, 2025)
BackgroundPsychomotor disturbance has long been observed in major depressive disorder (MDD) and is thought to be a key indicator of illness course. However, dominant methods of measuring psychomotor disturbance, via self-report and clinician ratings, often lack objectivity and may be less sensitive to subtle psychomotor disturbances. Furthermore, the neural mechanisms of psychomotor disturbance in MDD remain unclear.MethodsTo address these gaps, we measured psychomotor agitation via a force variability paradigm and collected resting fMRI in 47 individuals with current MDD (cMDD) and 93 individuals with remitted MDD (rMDD). We then characterized whether resting-state cortico-cortical and cortico-subcortical connectivity related to force variability and depressive symptoms.ResultsBehaviorally, individuals with cMDD exhibited greater force variability than rMDD individuals (t(138) = 3.01, p = 0.003, Cohen’s d = 0.25). Furthermore, greater force variability was associated with less visuomotor connectivity (r(130) = −0.23, p = 0.009, 95% CI [−0.38, −0.06]). Visuomotor connectivity was significantly reduced in cMDD relative to rMDD (t(130) = −2.77, p = 0.006, Cohen’s d = −0.24) and mediated the group difference in force variability (ACME β = −0.06, 95% CI [−0.16, −0.01], p = 0.04).ConclusionsOur findings represent a crucial step toward clarifying the pathophysiology of psychomotor agitation in MDD. Specifically, altered visuomotor functional connectivity emerged as a candidate neural mechanism, highlighting a promising direction for future research on dysfunctional visually guided movements in MDD.
Gesehen am 14.01.2026